ANALISIS HUBUNGAN DWELLING TIME TERHADAP PENDAPATAN JASA PELAYANAN CONTAINER DI PELABUHAN SURABAYA - Muhammad Fichri Hidayat; Danis Maulana; Alfred Bawole (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2022)
In the IOT era, the development of a technology has grown rapidly in the world, especially in the industrial sector. Over time, the development of the freight forwarding industry has also experienced many improvements. According to the World Bank (2011), Dwelling time is the time calculated from the time a container is unloaded from the ship until the container leaves the port terminal through the main door. In this study using simple Linear Regression Analysis and the t test. The purpose of this research is to find out and explain the impact of Dwell time on income at PT. Surabaya Container Terminal. The results of this study indicate that the realization value of the average port residence time is 5 days and these figures exceed the target set by the government, which is 3 days.In the simple Linear Regression Test and the t test for the influence of Dwell time at the customs and post clearance stages in 2019-2021 the significance value and the t Dwell time test have an effect on Port Revenue.